Climate change and mountain pastoralism – the Shahsevan of Northwest Iran - Tahmasebi, Asghar; Ehlers, Eckart; Schetter, Conrad (ERDKUNDE, 2013)
High-mountain areas in arid environments are extremely sensitive indicators of sometimes only slight changes of precipitations and temperatures. This holds true especially for the so far under-researched mountain regions of Iran and its immediate neighbours. Climate change, however, is not the only consequence. Climate and environmental changes have deep impacts on the traditionally nomadic population, their economy and lifestyle. Thus, it is justified to speak of both ecological and socio-economic vulnerabilities that characterize the present-day development of Iran’s mountain regions. Regional focus of this study is the Sabalan Kuh (4811 m) mountain area in northwestern Iran and its forelands. The paper tries to combine meteorological measurement over a 40-year time span with in-depth analyses of nomadic perceptions, experiences and adaptations to the obvious trends of a rapidly changing natural environment. While temperature increases are statistically significant (tab. 3–6), the analysis of precipitation data is less predicative (Fig. 4). Altogether however, temperature and rainfall trends suggest an increasing exposure of the Shahsevan pastoral nomads to environmental stresses. Interestingly, our analysis of “objective” meteorological data shows a high degree of accordance with the empirically founded “subjective” experiences of the affected nomads. Thus, their adaptation strategies show a clear trend towards different forms of agro-pastoralism as a reaction to both climate change and changing political as well as socio-economic pressures. This paper therefore concludes that the combination of natural and social science research is not only possible, but indispensable in order to gain insights into the close interactions between nature and society. And it is mandatory in order to develop sustainable development strategies for regions and people under stress. This conclusion holds true especially for studies on local to regional scales!